Characterization of absorbed and produced constituents in goat plasma urine and faeces from the herbal medicine Gelsemium elegans by using high-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry. (24th April 2020) - Zuo, Meng-Ting; Wang, Zi-Yuan; Yang, Kun; Li, Yu-Juan; Huang, Chong-Ying; Liu, Yan-Chun; Yu, Hui; Zhao, Xue-Jiao; Liu, Zhao-Ying
Abstract: Ethnopharmacological relevance: Herbal medicine contains hundreds of natural products, and studying their absorption, metabolism, distribution, and elimination presents great challenges. Gelsemium elegans ( G. elegans ) is a flowering plants in the Loganiaceae family. The plant is known to be toxic and has been used for many years as a traditional Chinese herbal medicine for the treatment of rheumatoid arthritis, neuropathic pain, spasticity, skin ulcers and cancer. It was also used as veterinary drugs for deworming, promoting animal growth, and pesticides. At present, studies on the metabolism of G. elegans have primarily focused on only a few single available reference ingredients, such as koumine, gelsemine and gelsedine. Material and methods: The goal of this work is to elucidate the overall metabolism of whole G. elegans powder in goats using high-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (HPLC/QqTOF-MS). Results: Analyses of plasma, urine and fecal samples identified or tentatively characterized a total of 44 absorbed natural products and 27 related produced metabolites. Gelsedine-type, sarpagine-type and gelsemine-type alkaloids were the compounds with the highest metabolite formation. In the present study, most natural products identified in G. elegans were metabolized through glucuronidation and oxidation. Hydrogenation, dehydrogenation and demethylation also occurred. Conclusion: To our knowledge, this is the first report of the metabolite profiling of the G. elegans crude extract in goats, which is of great significance for a safer and more rational application of this herbal medicine. Graphical abstract: Image 1